Framework structured Ce2(C2O4)3·10H2O as a pseudocapacitive electrode of a hybrid (asymmetric) supercapacitor (HSC) for large scale energy storage applications - Singh M.; Mondal R.; Singh P.; Sharma N. (My University, 2025)
The electrochemical kinetics of the electrode material plays a crucial role in the development of various energy storage devices such as batteries, supercapacitors, and hybrid supercapacitors. Battery-type hybrid supercapacitors are envisaged as excellent candidates to bridge the performance gap between supercapacitors and batteries. Due to its open pore framework structure and more structural stability, porous cerium oxalate decahydrate (Ce2(C2O4)3·10H2O) is found here to be a potential energy storage material partly because of the presence of planer oxalate anions (C2O42−). Superior specific capacitance equivalent to 78 mA h g−1 (capacitance: 401 F g−1) at 1 A g−1 in the potential window of −0.3 to 0.5 V was observed in an aqueous 2 M KOH electrolyte. The predominant pseudocapacitance mechanism seems to operate because of the high charge storage capacity of the electrode as intercalative (diffusion control) and surface control charges stored by the porous anhydrous Ce2(C2O4)3·10H2O, which were close to 48% and 52%, respectively, at a 10 mV s−1 scan rate. Further, in the full cell asymmetric supercapacitor (ASC) mode in which porous Ce2(C2O4)3·10H2O is the positive electrode and activated carbon (AC) is the negative electrode, at the operating potential window of 1.5 V, the highest specific energy of 96.5 W h kg−1 and a specific power of ∼750 W kg−1 at 1 A g−1 current rate and a high power density of 1453 W kg−1, the hybrid supercapacitor still attains an energy density of 10.58 W h kg−1 at a 10 A g−1 current rate, which was obtained with a high cyclic stability. The detailed electrochemical studies confirm a high cyclic stability and a superior electrochemical charge storage property of porous Ce2(C2O4)3·10H2O making it a potential pseudocapacitive electrode for use in large energy storage applications. © 2023 The Royal Society of Chemistry.